Atomic insights into single-layer and bilayer germanene on Al(111) surface. (August 2020) - Muzychenko, D.A.; Oreshkin, A.I.; Legen'ka, A.D.; Van Haesendonck, C.
Abstract: The artificial postgraphene two-dimensional (2D) materials termed 2D-Xenes, which consist of atoms arranged in atomically thin sheets with a honeycomb lattice, have received extensive attention because of their unique electronic properties. Insights into the growth mechanism at the atomic scale constitute a major challenge for realizing high-quality 2D materials, as often the substrate and deposited atoms tend to form alloys. Here, we present evidence for intrinsic growth of germanene on Al (111), i.e . a postgraphene elemental 2D atomically thin sheet. The atomic-scale extra-high resolution scanning tunneling microscopy (STM) characterization supported by density functional theory–based calculations provides deeper insight into the true atomic arrangement for the (2 × 2)/Al (111) (3 × 3) and (√3 × √3)R (30°)/Al (111) (√7 × √7)R (±19.1°) germanene phases and unambiguously confirms their real 2D honeycomb nature, which till now lacks convincing experimental proof. First-principles calculations suggest atomic models with strongly buckled (2 × 2) and (√3 × √3)R (30°) germanene, with one of eight and one of six Ge atoms protruding upward, respectively, providing perfect atom-by-atom agreement with the true atomically resolved STM images for both germanene phases. Moreover, the experimentally observed phenomena of local removal of the buckling is consistent with the formation of a flat germanene structure. Furthermore, the formation of bilayer germanene with AB-stacking is demonstrated by means of re-deposition of germanene flakes from the STM tip on top of single layer germanene, indicating that germanene flakes can be easily torn off from the aluminum substrate and attached to the STM tip, retaining their 2D configuration. On the other hand, the formation of bilayer germanene suggests an increased electronic decoupling of the bottom germanene layer from the substrate, in contrast to single layer germanene. Graphical abstract: Image 1 Highlights: 2D atomically thin sheet of intrinsic germanene grown on Al (111) substrate. Extra-high resolution scanning tunneling microscopy visualization of true honeycomb atomic structure of germanene. Phenomena of local removal of the buckling yielding the formation of the flat germanene. The germanene sheets being torn off from the substrate exists in a free-standing 2D form. The formation of bilayer germanene suggests increased electronically decoupling from the substrate.